Climate agendas and instability green recovery programs and policy change in the EU and US - Wendler, Frank 1974- (Routledge research in comparative politics, 2025)
"This book examines the expansion of climate governance frameworks in the EU and US and their re-framing as part of green industrial programs. Addressing research on how vectors of stability and punctuation interact to advance or block policy progress, the book breaks new ground by presenting a theoretical framework suitable to integrate insights of comparative research and 'sui generis' accounts of climate policy as a variable and multi-dimensional issue. In its empirical part, it compares two contrasting trajectories of climate policy-making: namely, the adaptation of the European Green Deal agenda to the exogenous shocks of the Covid pandemic and war in Ukraine through its NextGen and RePowerEU programs; and the launch of green industrial policies targeting infrastructure (BIL) and inflation reduction (IRA) in the United States. Finally discussing to what degree the EU and US show signs of convergence towards a new type of climate policy from opposed starting points, the book identifies future research agendas around the topics of climate policy integration and politicization. This book will be of key interest to scholars, students and practitioners of climate change governance, European Union and US politics, environmental politics, and comparative politics"--